Antipsychotic treatment of community-dwelling and institutionalised patients with dementia in Germany. (3rd July 2018) - Hessmann, Philipp; Dodel, Richard; Baum, Erika; Müller, Matthias J.; Paschke, Greta; Kis, Bernhard; Zeidler, Jan; Klora, Mike; Reese, Jens-Peter; Balzer-Geldsetzer, Monika
Abstract: Objective: A restrictive use of antipsychotic drugs in patients with Alzheimer's disease (AD) is recommended due to an increased risk of cerebrovascular events and mortality. We hypothesise that the prescription of antipsychotics is associated with the patients' socio-demographic and clinical status (e.g., dementia severity). Methods: The prescription of antipsychotics was cross-sectionally evaluated in 272 community-dwelling and 123 institutionalised patients with AD across all severity stages of dementia. The patients' clinical characteristics covered the cognitive status, neuropsychiatric symptoms, daily activities, and quality of life (HrQoL). To determine associations with the use of antipsychotics bivariate and logistic regression analyses were conducted. Results: Totally, 25% of the patients were treated with antipsychotics. significantly less frequently than nursing home inhabitants (15.1% vs. 45.5%). Severely demented patients (MMSE 0–9) received antipsychotics most often (51.5%). Additionally, multiple regression analyses revealed a higher chance of prescription for participants with depressive symptoms (OR 2.3, 95% CI: 1.019–5.160) and those treated by neuropsychiatric specialists (OR 3.4, 95% CI: 1.408–8.328). Conclusions: Further longitudinal studies are required to assess the appropriateness of indications for antipsychotics and the reasons for a higher use in nursing home inhabitants and patients with severe dementia and depression.